Tlingit women and children in cedar canoes, Alaska (possibly Yakutat) ca. 1899 - Hester, Wilhelm, 1872-1947
Eight canoes filled with women and children in foreground, waterfront village in background across water. This photograph was probably taken during Hester's only trip to Alaska between 1898 and 1899 when he did some gold mining in the Klondike.